Web-based Application Design for Article 21 (for Civil Servant) Income Tax Reporting - Damayanti Damayanti; Tri Sandhika Jaya (Soshum: Jurnal Sosial dan Humaniora, 2019)
This research is based on the problems faced by almost all taxpayers (WP) of Government Employees (PNS) in Indonesia (especially in Bandar Lampung City), namely the difficulty of obtaining evidence of Article 21 income tax deductions on irregular earnings such as honorarium activities, performance allowances, should be made by the Treasurer whenever the WP earns the income. The treasurer only provides proof of income cuts on salary and routine allowances at the end of the year in the form of 1721A2 form. This problem is caused by the operator who input salary and income other than salary vary. To solve the problem, this research was made, with the aim of making the application of Article 21 Income Tax for Web-based PNS. By using waterfall method, this research resulted in a Web 21 Income Tax article program where all income earning operators either regular or irregular earnings can input to one program at the same time so that the end result is WP can access all evidence of Article 21 Income Tax either Final or the Non Final whenever and wherever the WP was located without having to come to the Treasurer. WP simply menggakses use the internet. With the development of this Web-based Article 21 PPh program can assist WP in reporting all of its income on its Annual Income Tax Return. and assist the government in reducing non-compliance with WP.